Considering Insulin Secretory Capacity as Measured by a Fasting C-Peptide/Glucose Ratio in Selecting Glucose-Lowering Medications - Fritsche, Andreas; Heni, Martin; Peter, Andreas; Gallwitz, Baptist; Kellerer, Monika; Birkenfeld, Andreas L.; Häring, Hans-Ulrich; Wagner, Robert (Experimental and Clinical Endocrinology & Diabetes, 2020)
Type 2 diabetes mellitus is a heterogeneous disease. Recently introduced new subclassifications promise more efficacious, tailored treatments which could complement current guidelines. In the differentiation of the new diabetes subphenotypes, assessment of insulin secretion is one of the essential components. Based on a large number of insulin secretion measurements, we propose fasting C-peptide/glucose ratio (CGR) as an adequate and practicable estimate of insulin secretion. CGR discriminates insulin deficiency from insulin hypersecretion. We suggest using insulin secretion, determined from CGR, as an essential input for therapeutic decisions at the beginning or modification of diabetes treatment. Furthermore, we propose 3 practical steps to guide decisions in the subtype-specific therapy of diabetes mellitus. The first step consists of detecting insulin deficiency indicated by a low CGR with the need for immediate insulin therapy. The second step is related to high CGR and aims at lowering cardiovascular risk associated with diabetes. The third step is the consideration of a de-escalation of glucose-lowering therapy in individuals with mild diabetes subphenotypes.
Keywords: insulin secretion; classification; subphenotype; C-peptide; treatment